PENGARUH KUALITAS JASA PENDIDIKAN TERHADAP KEPUASAN MAHASISWA DI UNIVERSITAS PENDIDKAN INDONESIA (Jurnal Tata Kelola Pendidikan, 2019)
This study entitled "Effect of Service Quality Education Student Satisfaction atthe university education of Indonesia ". The problem that the writer suggested inthis study is the student satisfaction about the quality of education services inuniversity education of Indonesia. In general, this study aims to determine theeffect of the quality of educational services to the student satisfaction at theuniversity education of Indonesia. The method used in this research is descriptivewith quantitative approach. Data collection techniques using a questionnaire thatis through online by using google form and a questionnaire to the respondentdirectly spread through print out the questionnaire, the number of questionnairesthat are spread as much as 99. The result of the calculation Weight Mean Score(WMS), showed that the quality of educational services included in the highcategory with a score of 3.69 and student satisfaction with a score of 3.68,including the high category. Analysis of the correlation between the quality ofeducational services to the student satisfaction has a strong relationship with acorrelation coefficient of 0.724. The regression equation of these two variables,namely Y = 10 175 + 0.820X, this means every one-unit change in the quality ofeducation services will provide updates to the satisfaction of the students of0,820. The results of significance test using t-test, namely t hitung (10,350)>t_tabel (1.984) means that there is a significant relationship between thevariables X and Y, then the coefficient of determination test results showed thatthe degree of connectedness between the quality of educational services to thestudent satisfaction affects 52.5 % while the remaining 47.5% influenced by otherfactors not examined. It is concluded that there is a positive and significantrelationship between the quality of education services to the satisfaction ofstudents in university education Indonesia.
Keywords: Quality of Educational Services; Student Satisfaction